Carbon dioxide pipelines are disproportionally located in marginalized communities in the United States - Julia A. Davis; Nafiseh Salehi; Liqing Li; Majid Shafiee-Jood (Communications Earth & Environment)
Abstract Carbon capture and storage and carbon dioxide removal technologies are pivotal for net-zero climate goals, requiring extensive carbon dioxide pipeline expansion across the U.S. However, as this network grows, concerns about safety and environmental justice intensify, due to insufficient regulations that may disproportionately expose marginalized communities to risks. Here, we empirically examine the environmental justice implications of existing and potential pipelines across communities. Using census-tract demographic data and pipeline spatial data, we applied LASSO regression to identify key demographic variables and incorporated them into binary logistic regression models to uncover if the locations of, and disadvantages associated with, carbon dioxide pipelines are equally distributed among different demographics. We find higher-income communities are less likely to host existing pipelines. Proposed pipelines are generally in areas with higher concentrations of Black residents, while areas with higher educational attainment show reduced likelihood. Using the Net Zero America study’s 2030 projection of carbon dioxide pipelines, we observe diminished impacts on higher-income and educated communities, although Black residents are less likely to have a pipeline in this scenario. All pipelines were more likely to be in rural areas. These findings reveal persistent demographic disparities in pipeline locations, underscoring concerns about resource accessibility and preparedness.